KUALITAS PELAYANAN PADA PERGURUAN TINGGI - Chairul Furqon (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Higher education institutions typify a social, formal institution encompassing internal and external relations among their stakeholder.s. At present, as free competition era endures, higher education institutions must be more responsive to their stakeholders, especially their internal stakeholders, i.e their students as their main asset. Therefore, identification of students’ perception toward institution’s performance is really imperative. This can be done through research on higher education institution’s service quality, where importance-performance analysis can be conducted from viewpoints: learning process, academic assistance, supporting educational resources, extracurricular activities, communication with institution administartors, and administrative services. Information on these aspects may become a gadget for evaluation. In the long run, it is expected to be able to revitalize higher education institutions to breed qualified graduates. Qualifiedgraduates which meet the business sector standard will eventually help develop the country’s competitiveness.